Apexification Management of Mandibular Second Premolar with a Blunderbuss Apex and Periapical Lesion of an Adult Patient - Chenshuang Li; Zhong Zheng; Xiaohong Deng; Lan Zhang; Baoyan Wang; Qingyu Guo; Min Zou (Case Reports in Dentistry)
Apexification is widely applied in teenager patients but rarely used in the adult population. Instead, artificial apical barrier with mineral trioxide aggregate (MTA) is clinically accepted, and spontaneous apical closure in nonvital immature teeth of adult patients has rarely been encountered while only apexification of the maxillary incisors in adult patients has been reported. The aim of this case report is to share a successful apexification application in the mandibular premolar with a blunderbuss apex and periapical lesion of an adult patient by using calcium hydroxide: radiographically, spontaneous hard tissue barrier has been established, and narrowing canal space and decreasing area of periapical shadow were documented without complications. Taken together, our study indicates that patient’s age and tooth position may not be the critical limitation for apexification.